BERAGAMA (ISLAM) DI TENGAH KEBERAGAMAN MASYARAKAT MELAYU BANGKA DALAM PERSPEKTIF DAKWAH KEAGAMAAN - Zayadi Zayadi (LP2M IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2022)
This article aims to explain how the social system in religious life, especially Islam in Bangka Belitung with the spectrum of diversity of Malay society in the perspective of religious preaching. This paper refers to the social system of the people of Bangka Belitung which consists of various ethnicities and religions. Of course, from the perspective of the religious proselytizing approach, this social system must be accompanied by the potential to realize the values of harmony and peace in the life of society and the state. In the perspective of da'wah and religion, this can be realized through 1) da'i and inclusiveness, 2) soothing da'wah materials, 3) and transformative da'wah. These three components are expected to be a reference or alternative in creating a solid and harmonious Malay community in the Bangka Belitung Islands.